Religions, beliefs, and education in the European Court of Human Rights : investigating judicial pedagogies - Fancourt, Nigel (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book represents an exposition of 'judicial pedagogies' as a new concept, and discusses juridical-educational issues in detail, through an analysis of the educational claims and assumptions of judges' decisions in the European Court of Human Rights (ECtHR). It sheds light on how, within courtrooms around the world, judges are increasingly being asked to decide upon issues of religion and belief in schooling, whether about admissions policies, curriculum planning, or pupils' and teachers' dress and jewellery. With key human rights principles are at stake, these proceedings are often fraught, clashing with strong opinions about education and schooling. Focusing on decisions made in the European Court of Human Rights (ECtHR), the author considers how the supranational court looks at these issues, and considers the ECtHR's role within the European Education space. Drawing upon research and scholarship surrounding these questions, the book surveys a series of educational issues, including curriculum and assessment, and takes a comparative approach in the discussion of case studies to demonstrate the variety and depth of judges' thinking. Thus, rather than considering the national or supranational legal principles and questions as jurisprudential issues, typically about religion or human rights, it reviews them from an educational perspective - as 'folk' theories of teaching and learning. Finally, it considers the implications of a theory of judicial pedagogy for the courts' educational competence in deciding on these matters, for education and educational policy research, the European education space, legal scholarship, and for legal and judicial education. Developing a novel and innovative approach to the pedagogies at play in a courtroom and providing fresh insights into the courts as agents of social change, it will appeal to scholars and researchers working across the disciplines of education, law, and religious studies"--
Religion in education : innovation in international research / edited by Joyce Miller, Kevin O'Grady, and Ursula McKenna -- Civility, religious pluralism, and education / edited by Vincent F. Biondo III and Andrew Fiala -- International perspectives on education, religion, and law / edited by Charles J. Russo -- Philosophies of Islamic education : historical perspectives and emerging discourses / edited by Nadeem Memon and Mujadad Zaman -- Comparative theology in the millennial classroom : hybrid identities, negotiated boundaries / edited by Mara Brecht and Reid B. Locklin -- God, education, and modern metaphysics : the logic of know "thyself" / Nigel Tubbs -- Migration, religion, and schooling in liberal democratic states / Bruce A. Collet -- Teaching religion using technology in higher education / edited by John Hilton III -- Public theology, religious diversity, and interreligious learning / edited by Manfred L. Pirner, Johannes Lähnemann, Werner Haussmann, and Susanne Schwarz -- Religious education as a dialogue with difference fostering democratic citizenship through the study of religions in schools / Kevin O'Grady -- Investigating political tolerance at conservative protestant colleges and universities / George Yancey, Laurel Shaler, and Jerald H. Walz -- Faith, diversity, and education : an ethnography of a conservative Christian school / Alison H. Blosser -- The First Amendment and state bans on teachers' religious garb analyzing the historic origins of contemporary legal challenges in the United States / Nathan C. Walker -- Improving the pedagogy of Islamic religious education in secondary schools : the role of critical religious education and variation theory / Ayse Demirel Ucan -- A history of Islamic schooling in North America mapping growth and evolution / Nadeem Ahmed Memon -- Teaching sexuality and religion in higher education : embodied learning, trauma sensitive pedagogy, and perspective transformation / edited by Darryl W. Stephens and Kate Ott -- Curriculum renewal for Islamic education critical perspectives on teaching Islam in primary and secondary schools / edited by Nadeem A. Memon, Mariam Alhashmi, and Mohamad Abdalla -- Islamic religious education in Europe : a comparative study / edited by Leni Franken and Bill Gent -- Teaching religious literacy to combat religious bullying insights from North American secondary schools / W. Y. Alice Chan -- Law, education, and the place of religion in public schools international perspectives / edited by Charles J. Russo -- Engaging with vocation on campus supporting students' vocational discernment through curricular and co-curricular approaches / edited by Karen Lovett and Stephen Wilhoit -- Equipping educators to teach religious literacy lessons from a teacher education program in the American South / Emile Lester and W. Y. Alice Chan -- Conceptualising religion and worldviews for the school opportunities, challenges, and complexities of a transition from religious education in England and beyond / Kevin O'Grady -- Inclusion and sexuality in Catholic higher education possibilities for institutional change / Mark A. Levand -- Religion and worldviews in education : the new watershed / edited By Liam Gearon, Arniika Kuusisto, Saila Poulter, Auli Toom and Martin Ubani -- Religions, beliefs, and education in the European Court of Human Rights investigating judicial pedagogies / Nigel Fancourt.
Keywords: European Court of Human Rights; Religious education -- Law and legislation -- Europe; Christian education -- Law and legislation -- Europe; Church and state -- Europe; Education -- Study and teaching -- Europe; EDUCATION / General; LAW / General; RELIGION / General